2009
DOI: 10.1016/j.cub.2009.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Flies Require Bilateral Sensory Input to Track Odor Gradients in Flight

Abstract: Summary Fruit flies make their living on the fly in search of attractive food odors. To maintain forward flight, flies balance the strength of self-induced bilateral visual motion [1] and bilateral wind cues [2], but it is unknown whether they use bilateral olfactory cues to track odors in flight. Tracking an odor gradient requires comparisons across two spatially separated chemosensory organs and has been observed in several walking insects [3–5], including Drosophila [6]. The olfactory antennae are separated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 30 publications
3
91
1
Order By: Relevance
“…One strategy is to turn upwind upon encountering an odor, because odors disperse downwind from the source. Previous studies have shown that Drosophila tend to fly or walk upwind in response to odor (Bhandawat et al, 2010; Budick and Dickinson, 2006; Duistermars et al, 2009; Steck et al, 2012; Thoma et al, 2014; van Breugel and Dickinson, 2014). Whereas flying insects must use visual cues to estimate wind direction from their own self-motion, walking insects can use mechanosensory cues to estimate wind direction (Bell and Kramer, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…One strategy is to turn upwind upon encountering an odor, because odors disperse downwind from the source. Previous studies have shown that Drosophila tend to fly or walk upwind in response to odor (Bhandawat et al, 2010; Budick and Dickinson, 2006; Duistermars et al, 2009; Steck et al, 2012; Thoma et al, 2014; van Breugel and Dickinson, 2014). Whereas flying insects must use visual cues to estimate wind direction from their own self-motion, walking insects can use mechanosensory cues to estimate wind direction (Bell and Kramer, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The FB also responds to a wide range of visual stimuli during flight, suggesting that it plays a role in flight motor control[23]. As olfactory cues can also direct flight, in addition to visual feedback[24, 25], the observed strong functional connections with the MB may reflect the FB’s role in integrating multimodal signals to control flight. Conversely, the AVLP, which has been shown to be involved in auditory processing[26], shows very low correlations with other auditory regions, such as the AMMC, and instead is highly correlated with its homolog, suggesting additional roles for these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Two antennae are required to facilitate odor localization in insects (Bell and Tobin 1981;Borst and Heisenberg 1982;Louis et al 2008;Duistermars et al 2009;Steck et al 2010). Furthermore, bilateral information is also employed in robot odor localization (Webster et al 2001).…”
Section: Bilateral Integration To Determine the Direction Of Locomotionmentioning
confidence: 99%